BUSSINESS ANALYSIS OF CASSAPRO UTILIZATION IN FEED ON KAMPONG CHICKEN IN MEDAN - D A Lumbangaol; A H Daulay; I Sembiring; T H Wahyuni; N Ginting (Talenta Publisher, 2018)
This study aims to determine the feasibility and efficiency of the economic value of the business of raising livestock chicken with cassapro utilization in diet at various levels in chicken age 0-12 week. Research was held at Medan city in December 2015 to March 2016. Research using a survey method to determine the price of feed used in research. Cassapro flour consists of level 0% (P0), 10% (P1), 20% (P2), 30% (P3), 40% (P4). Parameters observed that the total cost of production, income, analysis of profit / loss, Revenue / Cost ratio (R / C ratio) and Income Over Feed Cost (IOFC) for a period of 3 months. The results showed that the average income (Rp/100head/3month) were the highest in treatment P3 (279,468.89) and the lowest profit in treatment P0 (234,395.64), the average R / C ratio was the highest in treatment P3 (1.44) and the lowest in treatment P0 (1.34), the average IOFC for 3 months were highest in treatment P3 (196.123) and the lowest in treatment P1 (136.401). The conclusion from this study indicate cassapro as a mixture of feed ingredients in ration to the level of 40% can provide benefits feasibility applied to the community.